Hybridization due to changing species distributions: adding problems or solutions to conservation of biodiversity during global change? - Brennan,A; Woodward,G; Seehausen,O; Munoz-Fuentes,V; Moritz,C; Guelmami,A; Abbott,RJ; Edelaar,P (Evolutionary Ecology Research, 2014)
Background: Due to increasing global change, the rate of hybridization seemsto be increasing.Question: Is hybridization adding problems or solutions to the effects of globalchange on biodiversity?Methods: We divided ourselves into two independent groups. Each group listedtopics it thought appropriate. We then compared and combined the lists, extracting anatural structure of the topics. We next divided ourselves into three specializedsubgroups and discussed the topics in more depth. In a final plenary meeting, webrought ideas together, discussed open topics, identified consensus or differences ofopinion, and prepared a preliminary report.Results: Our lists of topics were highly similar, suggesting that we missed only afew topics. We agreed that it is important to consider hybridization in both its geneticand ecological contexts and with explicit attention paid to phylogenetic andbiogeographic history. It is also necessary to distinguish between underlyingprocesses and resulting consequences. Knowledge of the consequences ofhybridization is more developed in genetics than in ecology. We suggest thathybridization adds problems (loss of biodiversity, ecosystem degradation) as well assolutions (new adaptive variation, ecosystem robustness) to global change challenges.Which of these applies in a given case depends on its evolutionary and environmentalcontext, and on the objectives of conservation management. We provide five groupsof questions to stimulate further research.